Dependence of gas shale fracture permeability on effective stress and reservoir pressure: Model match and insights. (1st January 2015) - Chen, Dong; Pan, Zhejun; Ye, Zhihui
Highlights: A theoretical correlation between shale permeability and effective stress is derived. The model is capable of matching the experimental data for different gas shales. The correlation between fracture compressibility and shale properties is discussed. The correlation between shale permeability and reservoir pressure is derived. Abstract: Although permeability data for different gas shales have been reported previously and attempts have been made to match permeability with empirical correlations, theoretical studies of shale permeability modelling are lacking. In this work, the correlation between fracture permeability and effective stress is established for gas shales through theoretical derivation. This model is able to match the permeability data for different gas shales. The matching results for the gas shale studied show that the model coefficient, fracture compressibility, which decreases as initial shale permeability increases, is strongly affected by the flow directions and varies with the shale's mineralogical composition. Furthermore, the correlation between fracture permeability and reservoir pressure has also been established. Sensitivity study shows that fracture permeability may decrease significantly with the reservoir pressure drawdown. Moreover, the horizontal fracture permeability drop is found to be significantly affected by the Young's modulus' anisotropic ratio ( Eh / Ev ). The insights gained warrant further theoretical and experimental studies to evaluate shale fracture permeability.